Enhancing energy efficiency in residential buildings through the use of BIM: The case for embedding parameters during design. (September 2017) - Beazley, Scott; Heffernan, Emma; McCarthy, Timothy J.
Abstract: A building design is typically created by a collaboration of professionals. Whilst the advent of BIM tools makes the assessment of the performance of an iterative design possible, these tools are not commonly used, due to traditional practice prevailing, technical limitations including differing data formats, and industry resistance to innovation. Timely consistent feedback throughout the design process, as major design decisions are made, could enable the enhancement of energy efficiency. However, current design guidelines are typically not in digital rule form, preventing the automated checking and validation of developing design models. Furthermore, architectural design tools have poor connections to thermal and environmental analysis software, which is exacerbated by a lack of knowledge of the data requirements of other disciplines both upstream and downstream. This paper explores the potential for embedding parameters within architectural model files to enable the enhancement of energy efficiency at the design stage and through the design process. It explores the architectural to energy analysis data exchanges, and demonstrates the way in which energy efficiency parameters can be embedded within model files to inform decision making at the conceptual design stage. The paper found that by using tools readily available, it is possible to add value during the design process through the use of BIM, with improved design outcomes as the result. The need to develop new workflows between the disciplines as a result of this different approach was highlighted. This enhanced practice is more responsive and can support better communication within project teams through providing timely information and feedback, providing analysis before optimisation for energy efficiency.